G359 Rituximab In Nephrotic Syndrome. (7th April 2014) - Stallard, L; Dolan, N; Riordan, M; Waldron, M
Abstract : Aims: To assess the efficacy of rituximab at inducing and maintaining remission in nephrotic syndrome. Methods: A retrospective chart review of 13 patients with nephrotic syndrome who received rituximab in our hospital between September 2006 and October 2013. Results: We present 13 children with nephrotic syndrome who failed to maintain remission with other immunosupressive regimes. Mean age at diagnosis was 6.84 years (range 14 years – 2 years). Mean time period of nephrosis prior to rituximab was 5.84 years. Previous treatments: Tacrolimus (11/13) Mycophenolate (11/13) Cyclosporine A (11/13) Cyclophosphamide (6/13). 38% received all 4 immunosupressors. Of those that underwent biopsy: 2 MCD, 3 FSGS, 3 IgM nephropathy and 1 MPGN. Indications for Rituximab: steroid resistance (2/13), steroid dependent frequent relapse (8/13) and steroid dependent excessive steroid side effects (3/13). Rituximab dose was 375 mg/m 2 . 2 doses were administered while the 2 cases of MPGN received4 doses. Average number of relapses the year prior to Rituximab was 2.87, decreasing to 0.38 the year post. One steroid resistant patient did not achieve full remission. The mean dosage of steroids at time of first Rituximab was 0.27 mg/kg/d, decreasing to 0.06 mg/kg/d two months post. The mean length of time to stopping steroids was 4.63 months. B cell depletion was monitored in 11 patients (84.6%): 8 (72.7%) achieved complete B cell depletion. Six patients (46.1%) received a second cycle of Rituximab at a mean interval of 18.5 months (range 1224). All patients had B cell recovery prior to relapse. At most recent follow up 12 out of 13 patients remain on an immunosuppressor. Conclusion: Rituximab markedly decreased both the frequency of relapse and steroid dependency. Only one patient did not achieve remission post Rituximab; this patient was steroid resistant and did not have complete B cell depletion (B cells 2% at lowest count). 46% of patients required subsequent doses within 2 years, while 92% of patients remain on an immunosupressor. Optimal initial dosing of Rituximab to achieve B cell depletion and the need for ongoing immunosuppression post an adequate cycle needs to be reviewed.